2014
DOI: 10.11607/jomi.3242
|View full text |Cite
|
Sign up to set email alerts
|

Tolerance Measurements on Internal- and External-Hexagon Implants

Abstract: This assignment applies to all translations of the Work as well as to preliminary display/posting of the abstract of the accepted article in electronic form before publication. If any changes in authorship (order, deletions, or additions) occur after the manuscript is submitted, agreement by all authors for such changes must be on file with the Publisher. An author's name may be removed only at his/her written request. (Note: Material prepared by employees of the US government in the course of their official d… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
11
0

Year Published

2016
2016
2022
2022

Publication Types

Select...
5
2
1

Relationship

1
7

Authors

Journals

citations
Cited by 24 publications
(12 citation statements)
references
References 0 publications
1
11
0
Order By: Relevance
“…The mismatch between implant and abutment components (micro-gap) can be increased by micromotion phenomena under functional loading, which could result in increased friction, microleakage, material wear, titanium particle release and screw loosening [ 68 , 71 , 72 , 73 , 74 , 75 , 76 , 77 , 78 , 79 , 80 ]. Braian et al [ 71 ] evaluated the horizontal micro-gap between abutments and implants with external and internal hexagonal connections. They found the smallest micro-gap for prefabricated gold abutments (less than 50 μm) placed on implants with external hexagon compared to prefabricated plastic cylinders (less than 130 μm) placed on implants with internal hexagonal connections.…”
Section: Resultsmentioning
confidence: 99%
“…The mismatch between implant and abutment components (micro-gap) can be increased by micromotion phenomena under functional loading, which could result in increased friction, microleakage, material wear, titanium particle release and screw loosening [ 68 , 71 , 72 , 73 , 74 , 75 , 76 , 77 , 78 , 79 , 80 ]. Braian et al [ 71 ] evaluated the horizontal micro-gap between abutments and implants with external and internal hexagonal connections. They found the smallest micro-gap for prefabricated gold abutments (less than 50 μm) placed on implants with external hexagon compared to prefabricated plastic cylinders (less than 130 μm) placed on implants with internal hexagonal connections.…”
Section: Resultsmentioning
confidence: 99%
“…The results from Study I are only applicable to the specific components utilised. The findings from Study I and from other researchers [105,106] suggest clearances ranging from 22-130 µm between different implant components.…”
Section: Study Isupporting
confidence: 63%
“…For implant components the implant manufacturer designs both the connecting and receiving parts of the constructions, thus they have the possibility to calculate tolerances and clearance for both parts. Some authors have investigated the clearance between different implant components ranging from 22-130 µm [105,106].…”
Section: Production Tolerances In Dentistrymentioning
confidence: 99%
See 1 more Smart Citation
“…indicated that metallic components show lower tolerance than prefabricated plastic copings. [ 13 ] The use of plastic components versus metallic ones might impact the results of the study; however, no statistical difference was observed between the open-tray group (metallic components) and the closed-tray group (plastic components).…”
Section: Discussionmentioning
confidence: 99%